KOMPETENSI MANAJEMEN DOKTER DI FASILITAS PELAYANAN KESEHATAN PADA DAERAH TERTINGGAL DI INDONESIA: KEBUTUHAN DAN TANGGUNG JAWAB INSTITUSI PENDIDIKAN KEDOKTERAN - Fury Maulina; Riris Andono Ahmad; Mubasysyir Hasanbasri (Journal of Health Service Management, 2016)
Background: challenges to work in underdeveloped areas andpeople's expectations of the quality of healthcare requiresdoctors who have public health program managementcompetencies. Objectives: identify perception of the needs and responsibilityof medical education institution to meet the managementcompetencies. Method: a mixed method study mixed method with sequentialexploratory. Results: Communication skills and respecting the right ofothers are the most needed competencies and the less neededcompetency is become chairman/leader of an activity.Competency to manage the organization's finances have notbeen met by a medical education institution and competencywhich has been met by medical education institutions is anupdating of medical knowledge actively. Conclusion: doctors need management competencies whileon duty in underdeveloped areas, but medical educationinstitutions are not yet fully meet its responsibilities in thefulfilment of these competencies.